Assessment of aortic dilatation in Chinese children and adolescents with Turner syndrome: a single center experience - Wei Su; Longwei Sun; Zhuoguang Li; Xia Liu; Longjiang Zhang; Xiu Zhao; Shumin Fan; Boning Li; Ying Xie; Weiwei Xiao; Zhe Su (BMC, 2024)
Abstract Background Patients with Turner syndrome (TS) face an increased risk of developing aortic dilatation (AD), but diagnosing AD in children presents greater complexity compared to adults. This study aimed to investigate the application of various assessment indicators of AD in Chinese children and adolescents with TS. Methods This study included TS patients admitted to Shenzhen Children's Hospital from 2017 to 2022. Cardiovascular lesions were diagnosed by experienced radiologists. Patients without structural heart disease were divided into different body surface area groups, then the Chinese TS population Z-score (CHTSZ-score) of the ascending aorta was calculated and compared with other indicators such as aortic size index (ASI), ratio of the ascending to descending aortic diameter (A/D ratio), and TSZ-score (Quezada's method). Results A total of 115 TS patients were included, with an average age of 10.0 ± 3.7 years. The incidences of the three most serious cardiovascular complications were 9.6% (AD), 10.4% (coarctation of the aorta, CoA), and 7.0% (bicuspid aortic valve, BAV), respectively. The proportion of developing AD in TS patients aged ≥ 10 years was higher than that in those < 10 years old (16.6% vs. 1.8%, P = 0.009), and the proportion of patients with CoA or BAV who additionally exhibited AD was higher than those without these conditions (31.6% vs. 5.2%, P < 0.001). The ASI, A/D ratio, TSZ-score, and CHTSZ-score of the 11 patients with AD were 2.27 ± 0.40 cm/m2, 1.90 ± 0.37, 1.28 ± 1.08, and 3.07 ± 2.20, respectively. Among the AD patients, only 3 cases had a TSZ-score ≥ 2, and 2 cases had a TSZ-score ≥ 1. However, based on the assessment using the CHTSZ-score, 6 patients scored ≥ 2, and 5 patients scored ≥ 1. In contrast, the TSZ-score generally underestimated the aortic Z-scores in Chinese children with TS compared to the CHTSZ-score. Conclusions The applicability of ASI and A/D ratio to children with TS is questionable, and racial differences can affect the assessment of TSZ-score in the Chinese population. Therefore, establishing the CHTSZ-score specifically tailored for Chinese children and adolescents is of paramount importance.